2. Pengaruh Konsentrasi Enzim Papain terhadap Kadar Proksimat dan Nilai Rendemen Hidrolisat Protein Ikan Bandeng (Chanos chanos Forks) - Ima Wijayanti; Romadhon Romadhon; Laras Rianingsih (Fakultas Perikanan Universitas Pekalongan, 2016)
Milkfish with high protein content has potential as the raw material of HPI and HPI review of the fish has not been implemented. This study aims to determine the effect of the concentration of the enzyme papain to the quality of the protein hydrolyzate of fresh milkfish (Chanos Chanos Forsskal). This study was conducted laboratory experimentally. The trial design used in this study was complete random design to analyze the effect of papain enzyme concentrations (4%, 5%, and 6%) toward the quality of protein hydrolyzate of milkfish. Protein hydrolyzate of milkfish could be produced by enzymatic hydrolysis using papain enzyme. The observed parameters were the yield and the proximate level (level of protein, fat, water, and ash). Type of enzyme and concentration had significant effect toward the proximate level of protein, fat, water, and yield, but not significant toward the level of ash. The optimal condition to hydrolyze milkfish flesh into protein hydrolyzate was by using papain enzyme with concentration of 5% (b/v). Keyword: Milkfish, hydrolyzate of protein, enzyme papain